CsPbBr3 Perovskite Quantum Dot Light‐Emitting Diodes Using Atomic Layer Deposited Al2O3 and ZnO Interlayers. Issue 1 (10th January 2020) - Yun, Hwang-Sik; Noh, Kyeongchan; Kim, Jigeon; Noh, Sung Hoon; Kim, Gi-Hwan; Lee, Woongkyu; Na, Hyon Bin; Yoon, Tae-Sik; Jang, Jaeyoung; Kim, Younghoon; Cho, Seong-Yong
Abstract : Most perovskite quantum dot light‐emitting diodes (PQD‐LEDs) are fabricated by vacuum processes, because PQDs are generally damaged by polar solvents which are typically used as the solvent for charge transport layer. To prevent photoluminescence quenching by polar solvent, Younghoon Kim, Seong‐Yong Cho, and co‐workers (article number 1900573 ) introduce atomic layer deposition (ALD)‐processed passivating layers between PQD layer and electron transport layer. The ALD‐Al2 O3 layers show excellent passivating effect from polar solvent and diethyl zinc. Furthermore, the bi‐layer architecture, ALD‐ZnO layer on ALD‐Al2 O3, is introduced – to not only overcome the insulating properties of Al2 O3, but also provide better contact resistance with spin‐coated ZnO nanoparticles. Bi‐layer PQD‐LEDs show significantly enhanced performance because of better electron transporting ability and higher power efficiency compared to the case when ALD‐Al2 O3 or ALD‐ZnO interlayer is used solely.